CONTINUITIES AND CHANGES IN THE STRUCTURE OF CERAMIC DESIGN: A RECORD OF MIGRATION AND SOCIAL CHANGE IN THE RIO GRANDE PUEBLOS. (May 2014) - Washburn, Dorothy K.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper traces migration and social adaptation in the northern Ancestral Pueblo Southwest during the thirteenth to sixteenth centuries from the perspective of continuities and changes in the structure of ceramic design. During the Coalition period cultural continuities are recorded in the patterns and structures between McElmo B/W and Santa Fe B/W and between Mesa Verde B/W and Galisteo B/W. Migrants from the Four Corners initially continued making their homeland decorative styles in their new homes on the Rio Grande. The designs, constructed by one-dimensional bifold rotation, are structural metaphors for the multiple reciprocities that organized kin relationships in the unit pueblo communities of their Four Corners homeland. Subsequently, during the Classic period coincident with the construction of large plaza-oriented towns there is a structural shift to finite design organization that, like designs in the earlier pithouse horizon, signals the adaptive role of the household as the self-sufficient mobile subsistence and social unit. This shift has also been observed in architecture and subsistence activities.